Distribution of pancreas imaging agents with 11C-amino acids in mice - WU Li-sun; YANG Guo-dong; JIANG Mei-ling; DONG Cheng (Acta Pharmacologica Sinica; Vol 5, No 2 (June 1984): Acta Pharmacologica Sinica, 2016)
Seven groups of 8 mice were injected ip 5 mg/kg of atropine, scopolamine, anisodamine, anisodine, cuscohygrinyl acetylmandelate,and camptothecin, respectively. In each group, 4 mice received only one injection while the other 4 received one injection qd×3 d. Twenty-four hours later, all mice were injected iv colloidal 198Au 25μCi/kg. Ten minutes after the injection, their livers and spleens were taken for radioactivity assay. All the henbane drugs promoted the phagocytosis of in livers and spleens, especially in those given drugs qd×3 d. But camptothecin inhibited the phagocytosis.